The Accuracy of the Selection of Learning Models in Piano Teaching for Autistic Children at Blue Notes Music School - Marsoar, Albert Jamot; Retnowati, Tjut Etty; Lalan Erlani; Annisa, Auliya Ayu (Program Studi Pendidikan Musik, 2025)
This study aims to describe the process of selecting and implementing learning models in piano instruction for children with autism at Blue Notes Music School. The background of this research is rooted in the need to adapt music education strategies to meet the specific needs of students with autism spectrum disorder, ensuring effective and responsive learning. This research uses a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation involving one educator and three autistic students. The results show that the educator adopted a combination of the TEACCH and Applied Behavior Analysis (ABA) approaches, tailored to the students' visual, emotional, and behavioral needs. The selection process was conducted reflectively and based on the individual responses of students during lessons. The study concludes that the appropriate and adaptive choice of learning models can enhance focus, comfort, and participation of children with autism in piano learning.